2019
DOI: 10.1108/ijm-09-2017-0249
|View full text |Cite
|
Sign up to set email alerts
|

Job preferences of business and economics students

Abstract: Purpose The purpose of this paper is to elicit young economists’ job preferences through the use of a choice experiment (CE). Design/methodology/approach A CE conducted at a total of five universities in Spain, the Czech Republic and Germany. After estimating a random parameter logit model, the monetary value of the willingness to accept a specific job attribute is simulated. Findings The most important job characteristic, consistent across countries and universities, is a long-term career prospect at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
5
20
0
1
Order By: Relevance
“…en Administración de Empresas. Asimismo, mostraría coincidencia con una preferencia laboral vinculada a trabajos que brinden estabilidad con proyección de crecimiento, rasgo comúnmente destacado en el estudio de las predilecciones de los estudiantes de negocios (Bundy & Norris, 1992;Demel et al, 2019;Iacovou et al, 2011;Lim & Soon, 2006).…”
Section: Rankingunclassified
“…en Administración de Empresas. Asimismo, mostraría coincidencia con una preferencia laboral vinculada a trabajos que brinden estabilidad con proyección de crecimiento, rasgo comúnmente destacado en el estudio de las predilecciones de los estudiantes de negocios (Bundy & Norris, 1992;Demel et al, 2019;Iacovou et al, 2011;Lim & Soon, 2006).…”
Section: Rankingunclassified
“…Other studies in support of this position include Harun (2020), who insists that the starting salary is the main criterion that influences the career choice of students. Demel et al, (2019) also posit that the initial salary is a significant predicator of career interests in the accounting profession by accounting students. Nonetheless, studies such as Cottrel (2011) argues that the initial salary, although considered a significant criterion in career decisions of accounting graduates, but with time, other factors tend to override this importance.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The choice of outcomes was based on the stated purpose of quality traineeships increasing the employment prospects of young people and focussed on the probability of being hired in the months following the experience. A qualitative perspective was introduced to strengthen the meaning of successful career: reducing unemployment spells is a success, but finding a quality job and being persistently employed constitute better results (Demel et al , 2019 found that job continuity is the most important job attribute for university students across Europe).…”
Section: Data and Variables Descriptionmentioning
confidence: 99%